Laporan Kasus: Prolaps Uterus - Banjarnahor, Dharma Putra Perjuangan; Viena, Windi Clara; Monica, Tasya; Ulhaq, Aura Dhiya (Universitas Ciputra Surabaya, 2025)
Uterine prolapse is a condition in which the uterus protrudes into or outside the vagina. The prevalence of uterine prolapse is 50% in women who have given birth. Uterine prolapse is a spectrum of POP (Pelvic Organ Prolapse), characterized by uterine herniation or prolapse into the vagina due to the weakening of the pelvic floor muscles and other supportive tissues, such as ligaments and fascia. Several risk factors, such as aging, increased intra-abdominal pressure, or multiparity, can contribute to this condition. Diagnosis can be made using the Pelvic Organ Prolapse Quantification (POP-Q) system. Effective treatment needs early prevention through pelvic floor muscle exercise, as well as therapeutic options, including pessary ring use and surgery intervention. Uterine prolapse is not life-threatening, but it may cause significant morbidity and negatively impact the patient’s quality of life, both physically and psychologycally. This study described the case report of a 57-year old woman (P3A0) with a primary complaint of a protruding vaginal mass for the past 3 years. Based on the history and physical examination, the patient was diagnosed with stage 3 uterine prolapse. The inspection indicated a history of pessary therapy without improvement of subjective complaints. The patient was hospitalized and scheduled for a total transvaginal hysterectomy with anterior and posterior colporrhaphy. The clinical prognosis following total transvaginal hysterectomy was favorable, with improvement in functional outcomes, resolution of prolapse symptoms, improved quality of life, and reduced risk of recurrence in postmenopausal women.